Self-Reliance sebagai Strategi Pembangunan Ekonomi Ghana pada Post Covid-19 Era - Purnomo, Muhammad Aditya (Global and Policy Journal of International Relations, 2021)
ABSTRACT In 2019, Ghana was projected as the fastest growing economy in the world. Since 2017, Ghana has been consistently placed among top 10 of the fastest growing economies in Africa. However, the arrival of COVID-19 pandemic since December 2019 from Wuhan, China, made 2020 as difficult period not only for Ghana’s economy, but also worldwide. Impact to global economy caused by COVID-19 was regarded as the largest economic shock since last decades. Since the arrival of the virus in Ghana in March 2020, Ghana’s government has swiftly and responsively prepared and implemented strategic moves in order to respond against COVID-19 as well as recovering the country’s economy. The purpose of this paper is to describe in detail about Ghana’s economic recovery in post covid-19 era. Theory used in this paper is the theory of self-reliance. The writer argues that the important key in Ghana’s economic recovery policy in post covid era is the President of Ghana’s principle that the country must be able to fulfil its own needs while minimizing international aid dependency. It is done by strengthening domestic capabilities and resources, as well as fulfilling basic human needs for its citizen. Keywords: Covid-19; Economic Development Post Covid-19; Ghana; Self-ReliancePada tahun 2019, Ghana merupakan negara yang diproyeksikan sebagai fastest growing economy di dunia. Sejak tahun 2017, Ghana telah konsisten berada pada 10 besar negara dengan pertumbuhan ekonomi tercepat di Afrika. Namun kedatangan pandemi COVID-19 sejak Desember 2019 dari Wuhan, China, mengakibatkan periode 2020 sebagai masa sulit, tidak hanya bagi perekonomian Ghana, namun juga seluruh dunia. Hantaman terhadap ekonomi dunia akibat COVID-19 dikatakan sebagai largest economic shock sejak beberapa dekade terakhir. Sejak masuknya virus tersebut di Ghana pada Maret 2020, pemerintah Ghana telah secara cepat dan tanggap menyiapkan dan mengimplementasikan langkah-langkah strategis guna merespon COVID-19 serta memulihkan perekonomian negara. Tulisan ini bertujuan mendeskripsikan secara mendetail strategi pemulihan ekonomi Ghana dalam post covid-19 era. Teori yang digunakan pada tulisan ini adalah teori selfreliance. Penulis berargumen bahwa kunci penting dalam kebijakan pemulihan ekonomi Ghana dalam post covid era terletak pada prinsip Presiden Ghana, Nana Addo Dankwa Akufo Addo, bahwa negara harus mampu memenuhi kebutuhannya sendiri dengan meminimalisir ketergantungan bantuan internasional. Hal ini dilakukan melalui penguatan kapabilitas dan sumber daya domestik, serta pemenuhan basic human needs bagi masyarakat. Kata-kata kunci: Covid-19; Ghana; Pembangunan Ekonomi Paska Covid-19; SelfReliance  DOI : https://doi.org/10.33005/jgp.v9i2.3007